2016
DOI: 10.1371/journal.pone.0152211
|View full text |Cite
|
Sign up to set email alerts
|

Shaking B Mediates Synaptic Coupling between Auditory Sensory Neurons and the Giant Fiber of Drosophila melanogaster

Abstract: The Johnston’s Organ neurons (JONs) form chemical and electrical synapses onto the giant fiber neuron (GF), as part of the neuronal circuit that mediates the GF escape response in Drosophila melanogaster. The purpose of this study was to identify which of the 8 Drosophila innexins (invertebrate gap junction proteins) mediates the electrical connection at this synapse. The GF is known to express Shaking B (ShakB), specifically the ShakB(N+16) isoform only, at its output synapses in the thorax. The shakB2 mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 59 publications
3
36
0
1
Order By: Relevance
“…However, it seems likely that JONs form both electrical and chemical synapses onto B1 cells, because the very earliest part of the B1 step response (<10 ms from step onset) was affected by both the shakB mutation and the nicotinic antagonists. This conclusion is also consistent with anatomical data indicating that JONs form both gap junctions and chemical synapses with central neurons (Pezier et al, 2014; Pezier et al, 2016; Sivan-Loukianova and Eberl, 2005). …”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…However, it seems likely that JONs form both electrical and chemical synapses onto B1 cells, because the very earliest part of the B1 step response (<10 ms from step onset) was affected by both the shakB mutation and the nicotinic antagonists. This conclusion is also consistent with anatomical data indicating that JONs form both gap junctions and chemical synapses with central neurons (Pezier et al, 2014; Pezier et al, 2016; Sivan-Loukianova and Eberl, 2005). …”
Section: Resultssupporting
confidence: 92%
“…JONs express shakB , a gap junction subunit (Pezier et al, 2016), and so we tested the effect of a mutation in the shakB gene (the null allelle shakB 2 ; Baird et al, 1990). In B1 cells, stimulus-evoked responses were significantly reduced in the mutant.…”
Section: Resultsmentioning
confidence: 99%
“…We have shown previously that driving overexpression of the transcription factor En in the JO-A and -B subpopulations of JON afferents (using the JO15-GAL4 line [30]) causes the formation of new chemical synaptic connections between JO-B afferents and GF, in addition to expanding the population of dye-coupled afferents, and also increasing the length of medial GF dendrites [15]. Later observations suggested that, despite its apparent dissimilarity in structure and function, overexpression of the N+16 isoform of ShakB also had an identical effect on dye coupling [16]. Our hypothesis, therefore, is that overexpression of ShakB(N+16) will also cause the formation of new (mixed) synaptic connections between JON afferents and GF, resulting in the appearance of more putative active zones in contact with the GF dendrites in addition to the NB-coupling of more axons.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous work suggested that gap junction proteins can also affect synaptic connectivity at the JON-to-GF synapse. In the innexin study we observed that overexpression of the 'correct' ShakB isoform, ShakB(N+16), in a subset of JONs induces ectopic synaptic coupling, whereas expression of the 'wrong' isoform, ShakB(N), abolishes it entirely [16]. In an earlier paper we had shown that ectopic synaptic coupling could also be induced by overexpression of the transcription factor Engrailed (En) in those same sensory neuronsin that case we showed that it was accompanied by the de novo formation of chemical synapses, along with an increase in postsynaptic dendritic branching [15].…”
Section: Introductionmentioning
confidence: 96%
“…A subset of mechanosensory neurons in the head of the fly form electrical synapses in the brain with the giant fiber neuron, which in turn, has mixed synaptic connections in the thorax with motor neurons innervating the jump and flight muscles. RNAi of the fly innexin ShakB(N + 16), one of five possible transcripts of the shakB locus (Zhang et al, ), abolishes the sensory‐to‐giant fiber neuron synapses, and when ShakB(N + 16) was ectopically expressed among other mechanosensory neurons, which normally do not have electrical synapses with the giant fiber neuron, novel dye‐coupling and electrical transmission were established (Pézier et al, ). Interestingly, when another splice isoform, ShakB(N) was expressed by these same neurons, it was found that all gap junctions between the mechanosensory cells and the giant fiber neuron were abolished.…”
Section: Why So Many Leech Gap Junction Genes?mentioning
confidence: 99%